2008
DOI: 10.1007/s00122-008-0752-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of two loci that confer resistance to Asian rust in soybean

Abstract: Asian soybean rust (ASR) is caused by the fungal pathogen Phakopsora pachyrhizi Sydow & Sydow. It was first identified in Brazil in 2001 and quickly infected soybean areas in several countries in South America. Primary efforts to combat this disease must involve the development of resistant cultivars. Four distinct genes that confer resistance against ASR have been reported: Rpp1, Rpp2, Rpp3, and Rpp4. However, no cultivar carrying any of those resistance loci has been released. The main objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 38 publications
4
101
0
10
Order By: Relevance
“…Genotypes PI 197182, PI 230971 and PI 417125 were classifi ed in group I, thus each one of these carry a single resistance gene located in the same linkage group of the Rpp2 locus already described in the literature. The Rpp2 locus was mapped on soybean linkage group J (Silva et al, 2008) and, with our data, it is not possible to know if the resistant genes derived from those PIs are alleles or if they are in different linked loci. Another resistant gene, though recessive, derived from PI 224270, was also mapped into this same linkage group .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Genotypes PI 197182, PI 230971 and PI 417125 were classifi ed in group I, thus each one of these carry a single resistance gene located in the same linkage group of the Rpp2 locus already described in the literature. The Rpp2 locus was mapped on soybean linkage group J (Silva et al, 2008) and, with our data, it is not possible to know if the resistant genes derived from those PIs are alleles or if they are in different linked loci. Another resistant gene, though recessive, derived from PI 224270, was also mapped into this same linkage group .…”
Section: Resultsmentioning
confidence: 88%
“…Until present studies on ASR races being carried out in Brazil, no results concerning these two isolates are conclusive. Reference should be also made to the study of Silva et al (2008), based on ITS sequence, which found 99.8% identity between the MT and MUT Zimbabwe isolates (GenBank accession no. AF333499).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rpp1 from PI 200492 (Hyten et al 2007), Rpp1-b from PI 594538A (Chakraborty et al 2009) and SBR resistance genes from PI 587886 and PI 587880A (Ray et al 2009) were mapped to the same region on soybean chromosome 18 [linkage group (LG) G]. Rpp2 (Silva et al 2008) was mapped on chromosome 16 (LG J), Rpp3 ) and Rpp? (Hyuuga) (Monteros et al 2007) were mapped on chromosome 6 (LG C2), Rpp4 (Silva et al 2008) and Rpp6 (Li et al 2012) were mapped to diVerent regions than Rpp1 on chromosome 18 (LG G), and Rpp5 (Garcia et al 2008) was mapped on chromosome 3 (LG N).…”
Section: Introductionmentioning
confidence: 99%
“…Rpp2 (Silva et al 2008) was mapped on chromosome 16 (LG J), Rpp3 ) and Rpp? (Hyuuga) (Monteros et al 2007) were mapped on chromosome 6 (LG C2), Rpp4 (Silva et al 2008) and Rpp6 (Li et al 2012) were mapped to diVerent regions than Rpp1 on chromosome 18 (LG G), and Rpp5 (Garcia et al 2008) was mapped on chromosome 3 (LG N). Due to the high virulence variability of P. pachyrhizi isolates, Rpp1, Rpp1-b, and Rpp3 already have been defeated in the Weld in Brazil (Ribeiro et al 2007;Yorinori et al 2005).…”
Section: Introductionmentioning
confidence: 99%